2022
DOI: 10.1002/smll.202104758
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Assembled Matrix System for Cell‐Bioengineering Applications in Different Dimensions, Scales, and Geometries

Abstract: Stem cell bioengineering and therapy require different model systems and materials in different stages of development. If a chemically defined biomatrix system can fulfill most tasks, it can minimize the discrepancy among various setups. By screening biomaterials synthesized through a coacervation‐mediated self‐assembling mechanism, a biomatrix system optimal for 2D human mesenchymal stromal cell (hMSC) culture and osteogenesis is identified. Its utility for hMSC bioengineering is further demonstrated in coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 57 publications
0
2
0
Order By: Relevance
“…Some researchers have modified hydrogels by incorporating different inorganic nanoparticles, such as hydroxyapatite (HA), 20 , 21 bioactive glass and β-tricalcium phosphate nanoparticles, 22 , 23 to improve the bone regeneration capacities of hydrogels. The results demonstrated that these fillers could, to some extent, change the hydrogel structure and improve its mechanical strength and osteoinductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have modified hydrogels by incorporating different inorganic nanoparticles, such as hydroxyapatite (HA), 20 , 21 bioactive glass and β-tricalcium phosphate nanoparticles, 22 , 23 to improve the bone regeneration capacities of hydrogels. The results demonstrated that these fillers could, to some extent, change the hydrogel structure and improve its mechanical strength and osteoinductivity.…”
Section: Introductionmentioning
confidence: 99%
“…Most researchers have used peptides derived from vitronectin (PQVTRGDVFTMP or KGGPQVTRGDVFTMP) for the preparation of peptide-conjugated surfaces [ [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] ], where hPSCs can proliferate. The peptide derived from fibronectin (RGDSP) is typically used to enhance the adhesion of any type of cell [ [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] ] but cannot effectively support hPSC proliferation on RGDSP-conjugated surfaces. The peptide derived from the laminin β4 chain (PMQJMRGDVFSP) was originally developed by Jia et al for the adhesion of hPSC-induced cardiomyocytes [ 24 ]; this peptide was effective for hPSC-derived cardiomyocyte adhesion (but not pluripotent hPSC adhesion) and was shown to be useful for hPSC proliferation on PMQJMRGDVFSP-conjugated surfaces in our previous studies [ 8 , 28 ].…”
Section: Resultsmentioning
confidence: 99%